Ultrasound in management of rheumatoid arthritis: ARCTIC randomised controlled strategy trial. (16th August 2016) - Haavardsholm, Espen A; Aga, Anna-Birgitte; Olsen, Inge Christoffer; Lillegraven, Siri; Hammer, Hilde B; Uhlig, Till; Fremstad, Hallvard; Madland, Tor Magne; Lexberg, Åse Stavland; Haukeland, Hilde; Rødevand, Erik; Høili, Christian; et al.
Abstract : Objective  To determine whether a treatment strategy based on structured ultrasound assessment would lead to improved outcomes in rheumatoid arthritis, compared with a conventional strategy. Design  Multicentre, open label, two arm, parallel group, randomised controlled strategy trial. Setting  Ten rheumatology departments and one specialist centre in Norway, from September 2010 to September 2015. Participants  238 patients were recruited between September 2010 and April 2013, of which 230 (141 (61%) female) received the allocated intervention and were analysed for the primary outcome. The main inclusion criteria were age 18-75 years, fulfilment of the 2010 American College of Rheumatology/European League Against Rheumatism classification criteria for rheumatoid arthritis, disease modifying anti-rheumatic drug naivety with indication for disease modifying drug therapy, and time from first patient reported swollen joint less than two years. Patients with abnormal kidney or liver function or major comorbidities were excluded. Interventions  122 patients were randomised to an ultrasound tight control strategy targeting clinical and imaging remission, and 116 patients were randomised to a conventional tight control strategy targeting clinical remission. Patients in both arms were treated according to the same disease modifying anti-rheumatic drug escalation strategy, with 13 visits over two years. Main outcome measures  The primary endpoint was the proportion of patients with a combination between 16 and 24 months of clinical remission, no swollen joints, and non-progression of radiographic joint damage. Secondary outcomes included measures of disease activity, radiographic progression, functioning, quality of life, and adverse events. All participants who attended at least one follow-up visit were included in the full analysis set. Results  26 (22%) of the 118 analysed patients in the ultrasound tight control arm and 21 (19%) of the 112 analysed patients in the clinical tight control arm reached the primary endpoint (mean difference 3.3%, 95% confidence interval −7.1% to 13.7%). Secondary endpoints (disease activity, physical function, and joint damage) were similar between the two groups. Six (5%) patients in the ultrasound tight control arm and seven (6%) patients in the conventional arm had serious adverse events. Conclusions  The systematic use of ultrasound in the follow-up of patients with early rheumatoid arthritis treated according to current recommendations is not justified on the basis of the ARCTIC results. The findings highlight the need for randomised trials assessing the clinical application of medical technology. Trial registration  Clinical trials NCT01205854 .